2021
DOI: 10.1136/bmjopen-2021-050139
|View full text |Cite
|
Sign up to set email alerts
|

Benefits and drawbacks of videoconferencing for collaborating multidisciplinary teams in regional oncology networks: a scoping review

Abstract: IntroductionVarious forms of videoconferenced collaborations exist in oncology care. In regional oncology networks, multidisciplinary teams (MDTs) are essential in coordinating care in their region. There is no recent overview of the benefits and drawbacks of videoconferenced collaborations in oncology care networks. This scoping review presents an overview of videoconferencing (VC) in oncology care and summarises its benefits and drawbacks regarding decision-making and care coordination.DesignWe searched MEDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
(108 reference statements)
2
8
0
Order By: Relevance
“…Lack of reimbursement was a barrier to attendance for isolated or community-based physicians. This is supported by prior literature where the equipment cost VMDTMs defer physicians from attending VMDTMs [12]. It is important to highlight that VMDTMs may be more cost-effective than IMDTMs in the long term [51,52].…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Lack of reimbursement was a barrier to attendance for isolated or community-based physicians. This is supported by prior literature where the equipment cost VMDTMs defer physicians from attending VMDTMs [12]. It is important to highlight that VMDTMs may be more cost-effective than IMDTMs in the long term [51,52].…”
Section: Discussionsupporting
confidence: 65%
“…The major technological issue highlighted in our studies was poor connectivity or limited bandwidth. Limited bandwidth prevents the proper functioning of audio and video components simultaneously, so, a bandwidth of 2 Mbps has been previously recommended [12].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a scoping review to study the benefits and drawbacks of videoconferencing in oncology networks, 25 it was found that there were several benefits to patients, such as less travel for diagnosis, better coordination of care, better access to scarce facilities and expertise, and treatment in their own community. Benefits for health care professionals included optimized treatment plans through multidisciplinary discussion of complex patients, an ability to inform all health care professionals simultaneously, enhanced care coordination, less travel, and continuous medical education.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical impact of specialized discussion forums and tumor boards has been well documented 3 . Videoconferencing among regional oncology networks has been mostly reported within high‐income countries (HICs), 4,5 and is associated with multiple benefits, including enhanced care coordination, optimization of treatment plans, and education of practitioners. Similar efforts within lower middle‐income countries (LMICs) are often limited to twinning initiatives between one LMIC center and an HIC center, that typically utilize videoconferencing with a focus on specific subspecialty case discussions 6–12 .…”
Section: Discussionmentioning
confidence: 99%